Determinants of Menstrual Health in Young Women Living in Darussalam Islamic Boarding School - Misniarti; Sutriyanti, Yanti; Haryani, Sri (Program Studi D III Kebidanan Akademi Kesehatan Sapta Bakti Bengkulu, 2022)
Background: Adolescence is also called a transitional period starting with children showing signs of pubertal development and continuing with changes from non-sexual to sexual. During menstruation, young women may face various problems related to menstrual disorders. The respondent in MTS school is 194 who live in Pondok Pesantren Darussalam. The government has a policy on reproductive health in adolescents which is listed in Law No. 23 of 1992 concerning health, in which the government makes preventive and promotive efforts. Nursing models of health belief models can be used to see the health of puberty in young women. Based on the description above, the researcher is interested in researching